Enterprise architecture in the higher education sector: A case study - Pedroso, Miguel Salvador (2022)
Organizations live in an ever changing environment where a robust architecture is needed in order to cope with such changes while maintaining the required standards to stay competitive. Enterprise Architecture is the discipline which studies an organization architecture, its components and their relationship with each other and with the outside context. It is a discipline which has been researched for the last 40 years but only recently started to show interest in exploring the frameworks and methods developed in the higher education sector. Therefore this research aims to explore the use of such practices in the higher education sector, applying it to a real-life scenario. Iscte, a university based in Portugal, as any other organization goes through regular changes to adapt to the outside environment which may cause dysfunctions in the university's social-cultural context as well as in the information systems. This work will apply the Zachman Framework to the university, more speci cally in the scope of the IT services in order to help them manage the on-going transformations and spot potential issues that already exist and may yet appear in the university architecture. A wiki style platform will be developed to host the framework and to allow stakeholders to get involved. A series of interviews with key players are conducted in order to get their perspectives into the current social and technological dimensions in the university. Recommendations to the current Iscte architecture are done based on the results from the framework and the interviews.